2019
DOI: 10.1186/s11671-019-3076-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Engineering for Highly Efficient Quasi-Two-Dimensional All-Inorganic Perovskite Light-Emitting Diodes via Adjusting the Ratio of Cs Cation

Abstract: Quasi-two-dimensional (2D) perovskites have received intensive attention as a new class of luminescent materials owing to large exciton binding energy and high photoluminescence efficiency. However, there usually contains a mixture of phases in these materials, and excessive low-dimensional phase perovskite is harmful for luminescence efficiency owing to the strong exciton-phonon quenching at the room temperature. Herein, a simple and effective method is proposed to suppress the growth of low-dimensional phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The obtained efficiency is significantly higher than that reported for PPA-Cs perovskite, where in all cases for different PPA:Cs ratios green emission was obtained and the highest efficiency achieved was 0.01%. 12 It should also be noted that FA-based devices exhibit multiple emission peaks consistent with the emission corresponding to n=2 phase and a large n or possibly 3D phase, while in MA-based devices we observe emission corresponding to n=3 phase, as illustrated in Fig. S10 †, Supporting Information.…”
Section: Resultssupporting
confidence: 65%
“…The obtained efficiency is significantly higher than that reported for PPA-Cs perovskite, where in all cases for different PPA:Cs ratios green emission was obtained and the highest efficiency achieved was 0.01%. 12 It should also be noted that FA-based devices exhibit multiple emission peaks consistent with the emission corresponding to n=2 phase and a large n or possibly 3D phase, while in MA-based devices we observe emission corresponding to n=3 phase, as illustrated in Fig. S10 †, Supporting Information.…”
Section: Resultssupporting
confidence: 65%
“…3a, there exists a mass of pinholes in pure PPA 2 (CsPbBr 3 ) 2 PbBr 4 film with relatively large grains (≈ 30 nm) which could cause severe current leakage and then limit the device performance. According to the previous reports, the quality of perovskite films can be improved by the incorporation of polymers [10,30]. Indeed, according to Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Hence, in our previous work, long-chain ammonium cation (phenylpropylammonium (PPA)) was introduced, enabling the formation of PPA 2 (CsPbBr 3 ) 2 PbBr 4 for quasi-2D PeLEDs through adjusting Cs ratio [30]. However, since there exist lots of pinholes in perovskite films, which cause serious leakage current, the performance of quasi-2D PeLEDs we reported still needs to be further improved for meeting the actual application.…”
Section: Introductionmentioning
confidence: 99%
“…All inorganic cesium lead halides (CsPbX3 , X = Cl, Br, I) and hybrid methylammonium lead halides (MAPbX3) are important functional materials [1][2][3][4][5] that can be synthesized as crystals, thinfilms, and nanomaterials with varied morphologies. 5,[6][7][8][9][10][11][12][13]14 Two dimensional (2D) plates and platelets are common, with thicknesses of only a few monolayers (ML) often observed, and lengths varied from nanometers to microns, which are formed during nucleation and growth, or self-assembled via solvent and or ligand mediated interactions. 4,[15][16][17][18][19][20] Studies have revealed that control over ligand types and stoichiometry, 20 as well as time and temperature of the synthesis can render various morphologies.…”
Section: Introductionmentioning
confidence: 99%